The Devil's Altar? Crime and the Early Modern Public House - Kümin, Beat (History compass, 2004)
Was the early modern public house really such a dangerous place, as Puritan preachers (and many historians) suggested? This article discusses offences by publicans and patrons. It argues that the evidence for crime needs to be carefully contextualised and that taverns could stabilise as well as threaten the social order.